Internalisasi Nilai-Nilai Moderasi Beragama Melalui Materi Pendidikan Agama Islam - Auliya, Safira Nur; Khojir, Khojir; Saleh, Khairul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Religious moderation is an effort to maintain religious harmony, especially in Indonesia as a country with different beliefs. In maximizing this, it is necessary to have an internalization effort in children from an early age, namely through Islamic Religious Education materials in schools. The purpose of this study was to determine the internalization of religious moderation values through Islamic Religious Education materials. This research uses the library research method. The results showed that the internalization carried out was in the form of value transformation stages, namely the explanation of the material from the teacher about Islamic Religious Education material, value transactions in the form of exemplary examples from teachers regarding the values ​​of religious moderation, and transinternalization of religious moderation values ​​in the form of a habituation process in teachers and students through the material contained in Islamic Religious Education lessons.